Polyfunctional Antigen Specific CD4+ T cell Responses in Patients With Human Immunodeficiency Virus/AIDS and Histoplasmosis Immune Reconstitution Inflammatory Syndrome. (29th June 2022) - Manion, Maura; Boulougoura, Afroditi; Naqvi, Nuha; Lage, Silvia Lucena; Richards, Elizabeth; Grivas, Christopher; Laidlaw, Elizabeth; Kuriakose, Safia; Ortega-Villa, Ana M; Tadros, Saber; Roby, Gregg; Rupert, Adam; et al.
Abstract: In the combination antiretroviral era, there are limited data regarding the pathogenesis of histoplasmosis immune reconstitution inflammatory syndrome (IRIS) in people with human immunodeficiency virus (HIV). We immunologically characterized 10 cases of histoplasmosis, 4 of whom developed histoplasmosis IRIS. CD4+ T cells in histoplasmosis IRIS demonstrated a significant polyfunctional cytokine response to histoplasma antigen.